Effectiveness of core stability exercise for knee joint osteoarthritis: A review - Muhammad Deyu Wisnubrata; Rahmat Sayyid Zharfan (Universitas Muhammadiyah Surabaya, 2020)
Abstract Background: The knee joint is a weight-bearing support joint that often affected by osteoarthritis. Knee joint osteoarthritis is characterized by pain in a movement that disappears when resting, joint stiffness especially after prolonged resting or waking up, crepitations, and can be accompanied by synovitis with or without joint fluid effusion. If the patient was passive, did not do exercises, muscle atrophy can occur, which will worsen the stability and function of the joint. Other consequences that can disrupt daily activities to the most severe feature, such as an inability to walk. Objective: To discuss the role of core stability exercise for pain reduction in osteoarthritis. Method: This type of study is a literature review. Result: The goals of core stability exercise include: increasing muscle strength, improving posture, reducing pain, increasing ability, and functional mobility in patients. The provision of core stability exercise has a relationship between core stability with hip, knee, and ankle. This is because all parts of the body are connected to each other, both directly and indirectly. If the core muscle is strong, the muscles of the hip, knee, and ankle will also be strong. Conclusion: Core stability exercise is potential in the management of knee osteoarthritisKeywords: core stability exercise, joint, knee, osteoarthritis